Estimation of the helium ion density distribution in the plasmasphere based on a single IMAGE/EUV image. Issue 5 (19th May 2014) - Nakano, S.; Fok, M.‐C.; Brandt, P. C.; Higuchi, T.
Abstract We have developed a technique by which to estimate the spatial distribution of plasmaspheric helium ions based on extreme ultraviolet (EUV) data obtained from the IMAGE satellite. The estimation is performed using a linear inversion method based on the Bayesian approach. The global imaging data from the IMAGE satellite enable us to estimate a global two‐dimensional distribution of the helium ions in the plasmasphere. We applied this technique to a synthetic EUV image generated from a numerical model. This technique was confirmed to successfully reproduce the helium ion density that generated the synthetic EUV data. We also demonstrate how the proposed technique works for real data using two real EUV images.